PREVALENCE OF SEXUAL HARASSMENT IN PUBLIC TRANSPORTATION AMONG FEMALE STUDENTS OF A PUBLIC COLLEGE AT BHARATPUR, NEPAL - Wagle , Rabina; Joshi , Alisha; Thapa , Taniya; Sigdel , Dipa; Nepal , Sarita (Journal of Chitwan Medical College, 2022)
Background: Sexual harassment in public transportation has been recognized as a worldwide serious problem, particularly among women. However, the exact figure of the sexual harassment in transit places is still unknown. Therefore, this study aims to identify the prevalence of sexual harassment in public transportation among the female students of a public college at Bharatpur. Methods: A descriptive cross-sectional study consisted of 196 female students who studied in the 12th standard of various academic streams of Saptagandaki Multiple Campus of Bharatpur. Stratified proportionate random sampling technique was used for selection of the desired sample. Structured questionnaire was used and data was collected from 2076/ 03/15 B.S to 2076/03/27 B.S through web - based survey. Data analysis was performed in SPSS version 20 for window using descriptive statistics. Results: Majority, i.e. 82.1% of the respondents experienced sexual harassment in public transportation of which 85.1% experienced verbal harassment followed by physical harassment (80.1%) and non- verbal harassment (70.8%). Male passengers were the main perpetrators involved in physical (82.8%), verbal (75.2%) and non- verbal harassment (81.6%). Furthermore, the study revealed that the highest (96.3%) of the participants did not file the complaint because of fear. Conclusions: Sexual harassment in public transportation was found to be significantly higher in female students. Therefore, government and concerned authorities need to adopt zero tolerance rules, regulation ad policies towards any form of sexual harassment in public spaces.